New Creep-Resistant Cast Alloys with Improved Oxidation Resistance in Water Vapor at 650–800°C - Dryepondt, Sebastien; Pint, Bruce A.; Maziasz, Philip J. (Frontiers in Materials, 2015)
Cast stainless steel CF8C-Plus (19wt.%Cr/12%Ni) has excellent creep properties, but limited oxidation resistance above 700ºC in environments containing H2O. One strategy to improve the alloy oxidation performance is to increase the Cr and Ni concentration. Two new alloys, with respectively 21wt%Cr-15wt%Ni and 22wt%Cr-17.5wt%Ni were therefore developed and their long-term oxidation behavior in humid air were compared with the oxidation behavior of five other cast alloys. At 650 and 700ºC, all the alloys formed internal Cr-rich nodules, and outer nodules or layers rich in Fe and Ni, but they grew a protective Cr-rich inner layer over time. At 750ºC, the lower alloyed steels such as CF8C-Plus showed large metal losses, but the two new alloys still exhibited a protective oxidation behavior. The 21Cr-15Ni alloy was severely oxidized in locations at 800ºC, but that was not the case for the 22Cr-17.5Ni alloy. Therefore, the two new modified alloys represent a potential operating temperature gain of respectively 50 and 100ºC in aggressive environments compared with the CF8C-Plus alloy.